SEQUENTIAL THERMAL ANALYSIS OF COMPLEX ORGANIC MIXTURES: PROCEDURAL STANDARDS AND IMPROVED CO2 PURIFICATION CAPACITY. Issue 2 (21st March 2023) - Hanke, Ulrich M; Gagnon, Alan R; Reddy, Christopher M; Lardie Gaylord, Mary C; Cruz, Anne J; Galy, Valier; Hansman, Roberta L; Kurz, Mark D
ABSTRACT: Sequential thermal analysis allows for deconvoluting the refractory nature and complexity of carbon mixtures embedded in mineral matrices for subsequent offline stable carbon and radiocarbon ( 14 C) isotope analyses. Originally developed to separate Holocene from more ancient sedimentary organic matter to improve dating of marine sediments, the Ramped Pyrolysis and Oxidation (RPO) apparatus, or informally, the "dirt burner" is now used to address pressing questions in the broad field of biogeochemistry. The growing interest in the community now necessitates improved handling and procedures for routine analyses of difficult sample types. Here we report on advances in CO2 purification during sample processing, modifications to the instrumentation at the National Ocean Sciences Accelerator Mass Spectrometry (NOSAMS) facility, and introduce sodium bicarbonate procedural standards with differing natural abundance 14 C signatures for blank assessment. Measurements from different environmental samples are used to compare the procedure to the different generations of sequential thermal analyses. With this study, we aim to improve the standardization of the procedures and prepare this instrumentation for innovations in online stable carbon isotopes and direct AMS-interface measurements in the future.